"Religion and nationalism in Souetheast Asia: Burma, Indonesia Philippines." - "Mehden, Fred Von Der." (Madison, 1963)
Religion and nationalism are two of the most potent and enduring forces that have shaped the modern world. Yet, there has been little systematic study of how these two forces have interacted to provide powerful impetus for mobilization in Southeast Asia, a region where religious identities are as strong as nationalist impulses. At the heart of many religious conflicts in Southeast Asia lies competing conceptions of nation and nationhood, identity and belonging, and loyalty and legitimacy. In this accessible and timely study.
Keywords: Political Science .